In situ mineralized PLGA/zwitterionic hydrogel composite scaffold enables high-efficiency rhBMP-2 release for critical-sized bone healing. (6th January 2022) - Liu, Peiming; Bao, Tianyi; Sun, Lian; Wang, Zeyi; Sun, Jin; Peng, Wan; Gan, Donglin; Yin, Guoyong; Liu, Pingsheng; Zhang, Wei-Bing; Shen, Jian
Abstract : In situ mineralized PLGA/PSBMA scaffold enables high-efficiency sustained release of rhBMP-2 (only 1.7% within 35 days) and robust healing of critical-sized (5 mm) nonunion calvarial defects in rats with an ultralow dosage of rhBMP-2 (150 ng per scaffold). Abstract : Osteoconductive and osteoinductive scaffolds are highly desirable for functional restoration of large bone defects. Here, we report an in situ mineralized poly(lactic- co -glycolic acid)/poly[2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide hydrogel (PLGA/PSBMA) scaffold as a novel high-efficiency carrier for recombinant human bone morphogenetic protein-2 (rhBMP-2) for bone tissue regeneration. By virtue of the oppositely charged structure, the zwitterionic PSBMA component is able to template well-integrated dense mineralization of calcium phosphate throughout the PLGA/PSBMA scaffold. The high affinity between rhBMP-2 and the mineralized matrix, combined with the capability of the zwitterionic hydrogel to sequester and to enable sustained release of ionic proteins, endows the mineralized PLGA/PSBMA scaffolds with high-efficiency sustained release of rhBMP-2 (only 1.7% release within 35 days), thus enabling robust healing of critical-sized (5 mm) nonunion calvarial defects in rats at an ultralow dosage of rhBMP-2 (150 ng per scaffold), at which level successful healing of critical-sized bone defects has never been reported. These findings show that the mineralized PLGA/PSBMA scaffold is promising for bone defect repair.